ENHANCING ENGLISH SPEAKING SKILLS OF GRADE 2 STUDENTS AT SDIT AWH THROUGH THE USE OF ENGLISH SONGS - Hidayat, Dadan; Adi, Wiruma Titian (INOVISH JOURNAL, 2024)
Abstract: This quasi-experimental study aimed to investigate the effectiveness of utilizing English songs in enhancing the English-speaking skills of Grade 2 students at SDIT AWH. The study involved 23 students who were subjected to a pretest-posttest design. The experimental group received instruction using English songs as a supplementary tool, while the control group followed the conventional teaching approach. Both groups were assessed using pertest and post-test speaking assessments. The findings revealed a significant improvement in the speaking skills of the experimental group compared to the control group. The results suggest that integrating English songs into language instruction can be an effective strategy for fostering English speaking proficiency among young learners. Implications for educators and recommendations for future research are discussed.